Clinical and antibacterial effect of tualang honey on pseudomonas keratitis in rabbit eyes - Punitan , S. Rajendran (2016)
BACKGROUND Pseudomonas aeruginosa is a common cause of microbial keratitis that can be sufficiently severe to cause a significant loss in visual acuity. Fluoroquinolones and aminoglycosides have a well-recognized clinical effectiveness against Pseudomonas-induced keratitis. As resistant pathogens are becoming more potent nowadays, the effectiveness of these antibiotics are reduced conspicuously. Tualang honey is produced by the rock bee (Apis dorsata), which builds hives high up in the branches of the tualang tree (Kompassia excelsa or Mengaris). It is used commonly as medicinal product and food in Malaysia. Tualang honey has both bactericidal and bacteriostatic properties against a wide range of bacteria. Besides that, it has anti-inflammatory and antioxidant properties which can facilitate wound healing. The potency of tualang honey against microorganisms suggest its potential to be used as an alternative therapeutic agent for certain medical conditions especially wound infection. OBJECTIVE To evaluate the clinical response and antibacterial effect of tualang honey as an alternative therapeutic agent in Pseudomonas-induced keratitis in rabbit eyes. METHOD An experimental randomized control trial in bacterial keratitis was performed in rabbit eyes between September 2014 and September 2016. A total of 30 rabbits' corneas were injected intrastromally with 1,000 colony forming units (CFU) of Pseudomonas aeruginosa in each eye. Twenty-four hours after the injection, the rabbits were randomised into three groups consisting of 10 rabbits in each group. Group A was treated with topical gentamicin 0.3%, Group B with topical tualang honey 30%, and Group C with combination of topical gentamicin 0.3% and tualang honey 30%. Topical antibiotics were then administered every 2 hours for the first 24 hours in all three groups. Subsequently, the medications were administered every 4 hours for 6 days. Clinical examination and mean slit lamp examination (SLE) of rabbits’ eyes were documented at day 1, 2, 3, 5 and 7 post induction of Pseudomonas aeruginosa. The eyes of each group were examined and recorded clinically using ulcer scoring system for corneal infiltrate, corneal ulcer, hypopyon and corneal perforation. At day 7 post induction of Pseudomonas aeruginosa, rabbits were euthanized and corneas were harvested to determine the mean CFU per cornea. The data collected were analyzed using Statistical Package for Social Science (SPSS) software version 22. Repeated measure ANOVA with multivariate analysis of variance were used for statistical analysis. For the data that was not normally distributed, Kruskal Wallis test was used. Thus the values were expressed as median (interquartile range). The p value of < 0.05 is considered statistically significant.